Pengaruh Motivasi Belajar dan Disiplin Belajar terhadap Hasil Belajar Siswa - Alfian Gunawan; RISNAWATI; GRANITA (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT This study aims to examine the effect of learning motivation and learning discipline on students’ learning outcomes. The research employed a quantitative approach with an ex post facto design. The sample consisted of 35 students selected using purposive sampling. Data were collected through questionnaires to measure learning motivation and learning discipline, as well as documentation to obtain students’ learning outcomes. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, preceded by prerequisite tests. The results indicate that learning motivation has a positive and significant effect on students’ learning outcomes. Learning discipline also has a positive and significant effect on students’ learning outcomes. Simultaneously, learning motivation and learning discipline significantly influence students’ learning outcomes, accounting for 53.7% of the variance, while the remaining 46.3% is explained by other factors outside the scope of this study. These findings confirm that learning motivation and learning discipline are crucial determinants of students’ academic achievement in madrasah education. This study is expected to contribute both theoretically and practically to the development of instructional strategies and character education in Islamic secondary schools Keywords: learning motivation, learning discipline, learning outcomes.